Programming languages : 17th Brazilian Symposium, SBLP 2013, Brasília, Brazil, October 3 - 4, 2013. Proceedings - Trinder, Phil; Bois, Andre Rauber (Lecture Notes in Computer Science, 2013)
This book constitutes the proceedings of the 17th Brazililan Symposium on Programming Languages, SBLP 2013, held in Brasília, Brazil, in September/October 2013. The 10 full and 2 keynote talks were carefully reviewed and selected from 31 submissions. The papers are organized in topical sections on program generation and transformation, including domain-specific languages and model-driven development in the context of programming languages, programming paradigms and styles, including functional, object-oriented, aspect-oriented, scripting languages, real-time, service-oriented, multithreaded, parallel, and distributed programming, formal semantics and theoretical foundations, including denotational, operational, algebraic and categorical, program analysis and verification, including type systems, static analysis and abstract interpretation, and programming language design and implementation, including new programming models, programming language environments, compilation and interpretation techniques.